2009
DOI: 10.2147/vhrm.s6787
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and clopidogrel hyporesponsiveness and nonresponsiveness in patients with coronary artery stenting

Abstract: Patients undergoing coronary artery stenting receive an antiplatelet regimen to reduce the risk of antithrombotic complications. Current guidelines recommend the use of acetyl salicylic acid (aspirin) and clopidogrel as evidenced by large clinical trials. There has been a concern about variable responses of patients to aspirin and clopidogrel which may predispose them to subacute stent thrombosis or late stent thrombosis. Up to 25% of patients with acute myocardial infarction (AMI) undergoing percutaneous coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 54 publications
1
45
0
Order By: Relevance
“…MPV, PDW, or PCT values were not different between groups, similar to Nada [21]'s study, which observed that diabetic patients receiving aspirin or clopidogrel did not show significant differences in MPV when compared with controls [19]. Hyperglycaemia may decrease the effectiveness of antiplatelet therapy by increasing reactive oxidant species and lead to aspirin resistance by binding to thromboxane receptors, whereas hypercholesterolaemia may blunt aspirin's effect on thrombin [23,24]. Genetics also play a role in patient response to aspirin as polymorphisms of platelets membranes postulated to cause aspirin resistance.…”
Section: Discussionsupporting
confidence: 73%
“…MPV, PDW, or PCT values were not different between groups, similar to Nada [21]'s study, which observed that diabetic patients receiving aspirin or clopidogrel did not show significant differences in MPV when compared with controls [19]. Hyperglycaemia may decrease the effectiveness of antiplatelet therapy by increasing reactive oxidant species and lead to aspirin resistance by binding to thromboxane receptors, whereas hypercholesterolaemia may blunt aspirin's effect on thrombin [23,24]. Genetics also play a role in patient response to aspirin as polymorphisms of platelets membranes postulated to cause aspirin resistance.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, it is imperative to understand this variable response or hyporesponsiveness to aspirin and clopidogrel in some patients. A clear definition of this response should be established and, based on this, one may then be able to categorize patients as a responders, hyporesponders, nonresponders, or resistant and thus manage their therapeutic regimen accordingly [9][10][11][12] .…”
Section: Resistancementioning
confidence: 99%
“…COX-1 is rapidly resynthesized by nucleated cells, such as endothelial cells, and therefore the effect of aspirin on nucleated cells lasts only for a relatively short time [4][5][6][7][8] . In contrast, the effect of aspirin on platelets (anucleate cells) lasts for the life of the platelets (7-10 d) [9] ( Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus on the characterization of aspirin and clopidogrel resistance, and its prevalence remains unclear [10,11]. This resistance is generally accepted to be characterized by incomplete suppression of platelet aggregation, as assessed by platelet-function tests.…”
Section: Introductionmentioning
confidence: 99%